THE IMPLEMENTATION OF IMAGINATIVE TECHNIQUE IN IMPROVING STUDENTS’ WRITING ABILITY ON DESCRIPTIVE TEXT AT THE SECOND GRADE OF MTs. MUHAMMADIYAH SIDOMULYO - Agus Salim Lamusu (Universitas Muhammadiyah Gorontalo, 2020)
The aim of these research was to get the data how Imaginative Technique Method can improve students’ writing ability on descriptive text at second grade MTs. Muhammadiyah Sidomulyo with target achieved 75% from number of students at second grade average 70. The research is class room research (CAR). Subject of this research is students’ second grade. The instruments of this research are test and observation sheet. The technique of analysis got by formula total students’ completeness divided total students’ multiplied one hundred percent. The result of this research point out Imaginative Technique method can improve students’ writing ability on descriptive text at second grade. This research carried out in two cycles where each cycle consists from two meeting. Cycle I grade average of students get 69.2 and cycle II grade average of student get 75.4. Keywords: Writing Ability, Descriptive Text, Imaginative Technique.